Short term effect of virtual reality on eye accommodative ability - Mukhtar, Mohd Syarifuddin; Che Azemin, Mohd Zulfaezal; Ithnin, Mohd. Hafidz; Mohd Tamrin, Mohd Izzuddin (RMP Publication, 2020)
Virtual reality (VR) is a fast-growing technology in the world today. Many countries use virtual reality for many purposes such as education, military and entertainment. Despite the benefits of VR, harmful effects of VR on the users are still inconclusive. With only a few reliable studies that investigate the effect of virtual reality on the users especially on the eyes, yet still there are a lot more things we do not know about the effects of VR. The purpose of this study was to compare the amplitude of accommodation before and after watching 3-dimesional (3D) movie utilizing VR and notebook (control group). Thirty-two participants volunteered in this study and all participants underwent amplitude of accommodation (AA) test using Royal Army Force (RAF) rule before and after watching three-dimensional (3D) movie for 30 minutes using VR and two-dimensional (2D) movie by laptop. The amplitude of accommodation between pre- and post-watching 3D movie on VR was insignificantly changed (p= >0.05). The similar trend was also found after 30 minutes watching movie using laptop (p= >0.05). The utilization of VR and laptop for 30 minutes did insignificantly alter the eye accommodation.